Transcanal Computed Tomography Views for Transcanal Endoscopic Lateral Skull Base Surgery: Pilot Cadaveric Study - Lubner, Rory J.; Barber, Samuel R.; Knoll, Renata M.; Kempfle, Judith; Lee, Daniel J.; Reinshagen, Katherine L.; Remenschneider, Aaron K.; Kozin, Elliott D. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective Transcanal endoscopic operative approaches provide for a minimally invasive surgical portal to the lateral skull base. Traditional preoperative imaging evaluation involves computed tomography (CT) acquisition in the axial and coronal planes that are not optimized for the transcanal surgical corridor. Herein, we describe a novel CT-based “transcanal view” for preoperative surgical planning and intraoperative navigation.Study Design Present study is a cadaveric imaging study.Methods Cadaveric temporal bones (n = 6) from three specimens underwent high-resolution CT (0.625 mm slice thickness). Using three-dimensional (3D) Slicer 4.8, reformatted “transcanal” views in the plane of the external auditory canal (EAC) were created. Axial and coronal reformats were used to compare and measure distances between anatomic structures in the plane of the EAC.Results The degree of oblique tilt for transcanal CT reformats was 6.67 ± 1.78 degrees to align the EAC in axial and coronal planes. Anticipated critical landmarks were identified easily using the transcanal view. Mean values were 8.68 ± 0.38 mm for annulus diameter, 9.5 ± 0.93 mm for isthmus diameter, 10.27 ± 0.73 mm for distance between annulus and isthmus, 2.95 ± 0.13 mm for distance between annulus and stapes capitulum, 5.12 ± 0.35 mm for distance between annulus and mastoid facial nerve, and 19.54 ± 1.22 mm for EAC length.Conclusion This study is the first to illustrate a novel “transcanal” CT sequence intended for endoscopic lateral skull base surgery. Future studies may address how incorporation of a transcanal CT reformat may influence surgical decision making.
Keywords: lateral skull base surgery; endoscopic; computed tomography; preoperative planning; transcanal surgery